Chasing the boogeyman : a novel - Chizmar, Richard, 1965- (Gallery Books, an imprint of Simon & Schuster, Inc., 2021)
"In the summer of 1988, the mutilated bodies of several missing girls begin to turn up in a small Maryland town. The grisly evidence leads police to the terrifying assumption that a serial killer is on the loose in the quiet suburb. But soon a rumor begins to spread that the evil stalking local teens is not entirely human. Law enforcement, as well as members of the FBI are certain that the killer is a living, breathing madman--and he's playing games with them. For a once peaceful community trapped in the depths of paranoia and suspicion, it feels like a nightmare that will never end"-- Provided by publisher.